Second Five-Year Plan (1956-61) Madras State the Nilgiris District - Planning Commission (Planning Commission, 1956)
The Nilgiris district lies between 11° 8' and 11° 55' of the northern latitude and 70° 13' and 77° 2' of the eastern longitude. Its boundaries on all the four sides are :—North : Malabar district, Mysore State and Coimbatore district; east : Coimbatore district; south : Coimbatore and Malabar districts and west : Malabar district. It has an area of 982 square miles and consists of three taluks of Gudalur, Ootacamund and Coonoor.
The Nilgiris District